Ecological Aspects of Hypsiboas faber (Anura, Hylidae) reproduction on the cove of Sítio Forte, Ilha Grande, Angra dos Reis, Brazil. - Lima, Mauro Sérgio Cruz Souza; Pederassi, Jonas; Souza, Carlos Alberto dos Santos (Comunicata Scientiae, 2013)
There are several anuran´s reproductive modes and even among the related species, there are slight differences in the larvae development. Were propose to analyze the nest distribution of Hypsiboas faber, in insular environment, as well as evaluate the structural and ecological aspects. Were calculated the nest area correlating to the number of eggs, adjusting the variables to the univariate straight-line equation, being the model tested through χ2. The density of nest distribution was also evaluated, besides the abiotic data, such as dissolved oxygen, pH and nitrite. It was observed the fidelity to the reproductive area during three years consecutives until the complete destruction of the place to real state use. The species had used an area of 11.28 m2, of which the center was occupied by a permanent puddle of 4 m2 in the outer dune. In the first sample period, it was found 23 nests, in the following period 15 and in the last period just 9 nests. Beyond the number of nests, were also observed the reduction of the area of the built nest from 0.30 m2 to 0.18 m2, being this decline probably related to the human occupation, culminating with the complete elimination of the reproductive area.